Control of wind energy systems - Mohamed Essif Barkhaya Yahya (Nanyang Technological University, 2020)
This final year project report aims to design a control system adapted to wind energy generation. Wind energy generation, similar to other renewable sources such as solar and hydro, generates an inconsistent electrical output. As such, control systems are needed to maintain the industrial parameters of generation. Such a task requires in-depth knowledge in not only control engineering but also renewable generation. This report will cover the fundamentals of control systems in electrical generation, focusing especially on the Load Frequency Control (LFC) aspect of power generation. It will showcase the individual effects of each control component followed by their combination into one system. It aims to conclude with a system that can be further built upon as control of renewable sources continues to be a topic that is becoming increasingly important due to rising global temperatures.